2017
DOI: 10.1007/s00702-017-1688-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuromelanin MRI is useful for monitoring motor complications in Parkinson’s and PARK2 disease

Abstract: Parkinson's disease (PD) is caused by the loss of dopaminergic neurons. Recently, specific T1-weighted magnetic resonance imaging (MRI) at 3 Tesla was reported to visualize neuromelanin (NM)-related contrast of dopaminergic neurons. Using NM-MRI, we analyzed whether disease severity and motor complications (MC) are associated with the degree of dopaminergic neuronal degeneration in the substantia nigra pars compacta (SNc) in patients with idiopathic PD (PD) and PARK2. We examined 27 individuals with PD, 11 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 31 publications
4
36
0
Order By: Relevance
“…It was also found that the SNc width was significantly negatively associated with the UPDRS motor score of the clinically most affected side in PD patients, in agreement with the growing clinical evidence which suggested that NM‐MRI changes were associated with disease severity . However, several studies revealed contradictory results . This discrepancy might partly be related to differences in the measurement methods and the recruited samples.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that the SNc width was significantly negatively associated with the UPDRS motor score of the clinically most affected side in PD patients, in agreement with the growing clinical evidence which suggested that NM‐MRI changes were associated with disease severity . However, several studies revealed contradictory results . This discrepancy might partly be related to differences in the measurement methods and the recruited samples.…”
Section: Discussionmentioning
confidence: 99%
“…A 3‐Tesla MRI unit was used to obtain a modified neuromelanin‐sensitive T1‐weighed fast‐spin echo sequence with an additional spectral presaturation inversion recovery pulse. We used a slightly modified version of the method reported by Schwarz and colleagues to quantify the high‐signal regions in the SNpc . We defined the high‐signal‐intensity region thought to reflect neuromelanin in the SNpc as the number of pixels exhibiting signals higher than +1.5 standard deviations (SDs) of the background signal, then used the high‐signal‐intensity region obtained by averaging the right and left SNpc as the NM‐SNpc area.…”
Section: Methodsmentioning
confidence: 99%
“…However, few studies have examined correlations between nigral degeneration and midbrain atrophy in PSP because conventional magnetic resonance imaging (MRI) techniques cannot visualize the SNpc in vivo. Recently, specific fast spin‐echo T1‐weighted MRI was reported to successfully visualize neuromelanin‐related contrast of dopaminergic neurons in the SNpc . Therefore, neuromelanin‐sensitive MRI (NM‐MRI) can be used to identify the dopaminergic neuronal degeneration underlying Parkinson's disease (PD) and other parkinsonian syndromes.…”
mentioning
confidence: 99%
“…Recently, it was reported that decreased NM‐SNc size on NM‐MRI correlates with the prevalence of MFs in idiopathic PD and PARK2 disease . In addition, Hong et al .…”
Section: Introductionmentioning
confidence: 97%
“…Specific fast spin‐echo T1‐weighted magnetic resonance imaging (MRI) at 3 Tesla (neuromelanin MRI; NM‐MRI) can detect neuromelanin in dopaminergic neurons in the SNc . Kuya et al .…”
Section: Introductionmentioning
confidence: 99%